Faecal calprotectin and faecal occult blood tests in the diagnosis of colorectal carcinoma and adenoma. Issue 3 (1st September 2001) - Tibble, J; Sigthorsson, G; Foster, R; Sherwood, R; Fagerhol, M; Bjarnason, I
Abstract : BACKGROUND AND AIMS: Testing for faecal occult blood has become an accepted technique of non-invasive screening for colorectal neoplasia but lack of sensitivity remains a problem. The aim of this study was to compare the sensitivity and specificity of faecal calprotectin and faecal occult blood in patients with colorectal cancer and colonic polyps. METHODS: Faecal calprotectin and occult blood were assessed in 62 patients with colorectal carcinoma and 233 patients referred for colonoscopy. The range of normality for faecal calprotectin (0.5–10.5 mg/l) was determined from 96 healthy subjects. RESULTS: Median faecal calprotectin concentration in the 62 patients with colorectal carcinoma (101 mg/l, 95% confidence interval (CI) 57–133) differed significantly from normal (2.3 mg/l, 95% CI 1.6–5.0) with 90% of patients having elevated levels (normal <10 mg/l) whereas only 36/62 (58%) had positive faecal occult bloods. There was no significant difference in faecal calprotectin levels when considering location or Dukes' staging of tumour. Percentage positivity of faecal occult bloods was significantly higher for Dukes' stage C and D cancers compared with Dukes' A and B. In the colonoscopy group, 29 patients with adenomatous polyps were detected in whom the median faecal calprotectin was 12 mg/l (95% CI 2.9–32). Sensitivity for detection of adenomatous polyps was 55% using the calprotectin method and 10% using faecal occult blood testing. The overall sensitivity and specificity of calprotectin for colorectal cancer and adenomatous polyps as a combined group was 79% and 72%, respectively, compared with a sensitivity and specificity of faecal occult blood of 43% and 92%. CONCLUSIONS: Faecal calprotectin is a simple and sensitive non-invasive marker of colorectal cancer and adenomatous polyps. It is more sensitive than faecal occult blood tests for detection of colorectal neoplasia at the cost of a somewhat lower specificity.